Mechanochemistry - a new powerful green approach to the direct synthesis of alkoxysilanes - Temnikov, Maxim N; Anisimov, Anton A; Zhemchugov, Pavel V; Kholodkov, Dmitry N; Goloveshkin, Alexander S; Naumkin, Alexander V; Chistovalov, Sergey M; Katsoulis, Dimitris; Muzafarov, Aziz M (Green chemistry : an international journal and green chemistry resource : GC, 2018)
The present work shows a new one-stage mechanochemical method for the direct synthesis of alkoxysilanes by silicon mechanoactivation followed by a reaction with an alcohol. Alkoxysilanes were obtained with nearly complete silicon and alcohol conversion. This method allows for a considerable simplification of the traditional multistage process by eliminating three stages that include silicon and catalyst preparation, and adapts it to green chemistry requirements. Vibration milling removed the oxide film, and the mechanoactivation of the large silicon fraction (1000-2000 μm) occurs in the reactor working space. Abrasion of the reactor walls and grinding bodies made of brass results in a developed catalytic surface on silicon, as it has been proven by a set of physical analytical methods such as scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), powder X-ray diffraction (PXRD), and X-ray photoelectron spectroscopy (XPS). The present work shows a new one-stage mechanochemical method for the direct synthesis of alkoxysilanes.